ADAPTATION OF PLANTS TO WINTER CLIMATIC ENVIRONMENTAL CONDITIONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article examines the adaptive capabilities of wintering crops in the conditions of irrigated lands of Uzbekistan to various abiotic (light, moisture, temperature, soil conditions, etc.) stresses affecting their preservation, growth, development, as well as the productivity of biomass, seeds and grains, and provides results on photosynthesis and respiration of winter crops. The results on biological and ecological characteristics of winter crops, as well as modern ideas about adaptive conditions in connection with their climatic capabilities are given.
Keywords: adaptation; autumn-winter and early spring period; safety; growth; development and productivity of plants